Between Centralisation and Autonomy ? Neoliberal Reforms of Education in Holland - Hildebrandt-Wypych, Dobrochna (INSTED: Interdisciplinary Studies in Education & Society, 2011)
The establishment of ?the society of knowledge? and ?economy of knowledge? in Holland has been in the centre of political debates on education since the 1980s of the 20th century. Adopting ?the economic perspective on education? earlier than in most Western European countries led to the victory of ?capitalism spirit? and ?a blind madness around efficiency? as a principal target of educational policy. A constant interest subject and reforming zeal in Holland have been the development of the system of measuring education quality and outcome-based education, where school reports on students? achievements are of key importance. The article presents selected aspects of building educational policy in the context of challenging ?learning? the new roles by schools and the increased responsibility for students? outcomes in accordance with national guidelines.